Destins familiaux brisés, destins familiaux croisés : une correspondance atlantique au XIXe siècle - Nathalie Dessens (Les Cahiers de Framespa)
This article examines the role of correspondences in the reconfiguring of Atlantic family relations. From a case study, the correspondence of Jean Boze to Henri de Sainte-Gême, archived at The Historic New Orleans Collection, in New Orleans, it examines the breaches of family ties in the Atlantic space in the era of the great migrations from Europe to the Americas and the reconfiguring that occurred in the Atlantic space, beyond mere transatlantic relationships. The article concludes on the role of correspondences in this reconfiguring and in the construction of an Atlantic family space.